Constitutionalism and some problems of ensuring the secular state of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
One of the most pressing problems of our time is that of the religious dimension of human life, which from the point of view of thelegal world, and carries out its legal science is formulated as a problem of the creation of a secular state. The author considers some ofthe problems of constitutionalism and ensure secular state of Kazakhstan.